Bewältigungskapazitäten im deutsch-polnischen Kulturvergleich - Schonder, Malgorzata (International Dialogues on Education Journal, 2017)
Malgorzata Schonder: Coping capacities in a German-Polish cultural comparison): Comparative cultural research reveals interesting differences in coping strategies between collectivist and individualistic cultures. However, there is no study in a German-Polish comparison so far. Therefore, the question of whether and to what extent coping capacities of young people from a more individualistic culture (such as Germany) and a more collectivist culture (such as Poland) differ from each other is examined here. According to the results, German students perceive stress more strongly than their Polish colleagues. One possible reason for this could be the training stress. With a university degree, Germans have better chances on the job market. This situation is associated with more competition and pressure to perform. Great importance is attached to individual career design. On the other hand, Poles notice that a graduation does not guarantee employment, and sometimes it even makes it difficult to find a job. The differences could also have their roots in the character of the two cultures, which were influenced by different attitudes to life and religious beliefs (protestantism vs. catholicism